Maritime Cyber Geopolitics: New Threats to Maritime Security in the Digital Era - Bagus Satrio Wicaksono; Asep Adang Supriyadi; Budiman Djoko Said; Pujo Widodo; Panji Suwarno (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
The digital era has transformed the maritime sector, integrating the oceans into the global internet network and creating new opportunities in trade and communications. However, this connectivity has also created significant cyber threats, leading to the emergence of cyber maritime geopolitics—the struggle for power at sea through information and communications technology (ICT). These threats include cyberattacks on maritime navigation systems, critical infrastructure, and data theft, all of which can disrupt global trade and trigger conflict. As maritime security becomes increasingly important, countries need to increase international cooperation, strengthen cyber defenses, and develop effective strategies to combat these threats. This paper aims to understand the challenges of cyber maritime geopolitics and proposes a multisectoral approach involving various stakeholders. Through comprehensive qualitative research, including a literature review and document analysis, this research identifies patterns and offers insights into strengthening maritime security policies. This research underscores the need for international collaboration, technological advances and investment in cybersecurity to ensure sustainable maritime security in the digital era. For Indonesia, a country with extensive maritime interests, implementing this strategy is very important to protect maritime infrastructure and maintain regional stability.